2007
DOI: 10.1093/rpd/ncm378
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering in concrete and wood: Part II--oblique incidence

Abstract: The knowledge of neutron reflection coefficients is of practical interest when projecting the shielding of radiotherapy rooms, since it is known that about 75% of the neutrons at the maze entrance of these rooms are scattered neutrons. In a previous paper, the energy spectra of photoneutrons were calculated, when reflected by ordinary, high-density concrete and wood barriers, using the MCNP5 code, considering normal incidence and neutron incident energies varying between 0.1 and 10 MeV. It was found that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This discrepancy stems from the fact that there are different neutron-neutron elastic and inelastic cross-sections for atoms constitute the studied HDC concretes. Studies attributed this difference in the reflected neutron fluence to the H content in different concretes and the neutron-neutron interaction cross-sections of other major components such as SiO 2 [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy stems from the fact that there are different neutron-neutron elastic and inelastic cross-sections for atoms constitute the studied HDC concretes. Studies attributed this difference in the reflected neutron fluence to the H content in different concretes and the neutron-neutron interaction cross-sections of other major components such as SiO 2 [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that about 75% of the neutrons at the maze entrance of these rooms are scattered neutrons [14,15]. Also, the studies have shown the fluence of scattered photons and neutrons per angle by different shielding materials as well as concretes depend on the composition of concretes and used shielding materials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that 75% of the neutrons at the entrance door of the maze are scattered neutrons. 16,17 Studies have also publicized that the intensity of photons and neutrons scattered at any angle by different radiation shielding materials and concretes depends on the composition of the concrete and shielding materials used.…”
Section: Introductionmentioning
confidence: 99%